2017
DOI: 10.1074/jbc.m116.758110
|View full text |Cite
|
Sign up to set email alerts
|

Myroilysin Is a New Bacterial Member of the M12A Family of Metzincin Metallopeptidases and Is Activated by a Cysteine Switch Mechanism

Abstract: Proteases play important roles in all living organisms and also have important industrial applications. Family M12A metalloproteases, mainly found throughout the animal kingdom, belong to the metzincin protease family and are synthesized as inactive precursors. So far, only flavastacin and myroilysin, isolated from bacteria, were reported to be M12A proteases, whereas the classification of myroilysin is still unclear due to the lack of structural information. Here, we report the crystal structures of pro-myroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 63 publications
0
16
0
Order By: Relevance
“…Target 2016‐07‐30_00000063_1 (Myroilysin, PDB ID 5CZW, Figure ) illustrates the details of the lDDT‐BS analyses. Myroilysin is a new bacterial member of the M12A family of metzincin metallopeptidases and activated by a cysteine‐switch mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…Target 2016‐07‐30_00000063_1 (Myroilysin, PDB ID 5CZW, Figure ) illustrates the details of the lDDT‐BS analyses. Myroilysin is a new bacterial member of the M12A family of metzincin metallopeptidases and activated by a cysteine‐switch mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…To date, the crystal structures of crayfish pro-astacin (PDB entry 3lq0; Guevara et al, 2010), human pro-meprin (PDB entry 4gwm; Arolas et al, 2012) and pro-myroilysin from two closely related bacterial species, Myroides profundi (PDB entry 5czw; Xu et al, 2017) and Myroides sp. CSLB8 (PDB entry 5gwd; Xu et al, 2017), have been reported, as well as their respective mature forms astacin (PDB entry 1ast; Gomis-Ru ¨th et al, 1993), meprin (PDB entry 4gwn; Arolas et al, 2012) and myroilysin from Myroides sp. CSLB8 (PDB entry 5zjk; Ran et al, 2020).…”
Section: Comparison With Other Astacin Latency Mechanismsmentioning
confidence: 99%
“…3(e)] from the bacterium Myroides sp. CSLB8 (37 residues, 1720 Å 2 ; Xu et al, 2017). Another example is the MMP karilysin [ Fig.…”
Section: Promirolysin Latency In the Context Of Other Mpsmentioning
confidence: 99%